Attenuated Disease in SIV-Infected Macaques Treated with a Monoclonal Antibody against FasL - Maria S. Salvato; C. Cameron Yin; Hideo Yagita; Toshihiro Maeda; Ko Okumura; Ilia Tikhonov; C. David Pauza (Clinical and Developmental Immunology)
Acute SIVmac infection in macaques is accompanied by high levels of plasma viremia that decline with the appearance of viral immunity and is a model for acute HIV disease in man. Despite specific immune responses, the virus establishes a chronic, persistent infection. The destruction of CD4+ and CD4- lymphocyte subsets in macaques contributes to viral persistence and suggests the importance of mechanisms for depleting both infected and uninfected (bystander) cells. Bystander cell killing can occur when FasL binds the Fas receptor on activated lymphocytes, which include T and B cell subpopulations that are responding to the infection. Destruction of specific immune cells could be an important mechanism for blunting viral immunity and establishing persistent infection with chronic disease. We inhibited the Fas pathway in vivo with a monoclonal antibody against FasL (RNOK203). Here we show that treatment with anti-FasL reduced cell death in circulating T and B cells, increased CTL and antibody responses to viral proteins, and lowered the setpoint viremia. By blocking FasL during only the first few weeks after infection, we attenuated SIVmac disease and increased the life span for infected and treated macaques.